Is a 4 J/cm2 PpIX-Weighted Simulated Daylight (SDL-PDT) Dose Still Efficient for Photodynamic Therapy of Actinic Keratosis? - Mathilde Fronville; Muriel Creusot; Serge R. Mordon (MDPI AG, 2023)
Background: Several solutions are now proposed to provide indoor illumination with so-called artificial white light or simulated daylight (SDL-PDT), resulting in an effective treatment for actinic keratosis (AK). However, the optimal PpIX-weighted light dose is still debated. Integrating the effective irradiance over the irradiation time yields the effective light dose, which is also known as the protoporphyrin IX-weighted light dose and is a key parameter for the efficacy of the treatment. Objectives: The paper aims to report the clinical outcomes of SDL-PDT when using the PpIX-weighted light dose of 4 J/cm2, in patients treated for AK lesions of the scalp or the face at our medical dermatology center (ClinicalTrials.gov NCT052036). Methods: A total of 30 patients (16 males, 14 females), with a mean age of 71.0 ± 10.2, with phototype 1 (16 patients) and phototype 2 (14 patients) with grade I-II AK were treated with a drug light interval (DLI) of 10 min and a light exposure of 35 min (Dermaris, Surgiris, Croix, France), corresponding to a PpIX-weighted light dose of 4 J/cm2. The primary endpoint was the cure rate of patients at six months post-treatment. Secondary endpoints included scores of pain, erythema, crusts, and discomfort during or/and post the treatment. Results: In total, 762 AK were treated. Six months following treatment, the cure rate of the patients was 77%. The median pain score was less than 1 out of 10 for most of the patients. Erythema was observed in all patients and lasted 3 days (±1.5 day). Crusts were seen in 28 patients. Discomfort was reported as mild or less in more than 97% of patients. Conclusions: The shortening of the PpIX-weighted light dose to 4 J/cm2, corresponding to an illumination duration of 35 min with the Dermaris, does not modify the efficacy of the SDL-PDT. This observation is in agreement with recent published data demonstrating that the light dose can be reduced. Furthermore, this clinical study confirmed that SDL-PDT is an effective and nearly painless treatment with minimal side effects for patients with AK lesions of the scalp.